2016
DOI: 10.1007/s00606-016-1287-5
|View full text |Cite
|
Sign up to set email alerts
|

Oil-resin glands in Velloziaceae flowers: structure, ontogenesis and secretion

Abstract: Many Velloziaceae flowers present conspicuous glands, whose taxonomic value has already been highlighted. However, until now, their micromorphology, anatomy and ultrastructure have not been investigated, nor have the natures and possible functions of their exudates. Our aim was to investigate distribution, ontogenesis, structure, and secretion mechanisms of glands of Barbacenia flava and Vellozia intermedia and to discuss their possible ecological functions. Samples were prepared according to standard methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The epithelial cells of mature oil glands of M. nigra share a number of common features with other metabolically active cells, such as a high density of ribosomes, a large nucleus-tocytoplasm volume ratio, and relatively small vacuoles (Fahn 1979;Evert 2006). In addition, the presence of endoplasmic reticulum tubular elements, leucoplast, and well-developed mitochondria with osmiophilic granulations has been described in glands producing terpenes (Turner et al 1999;Machado et al 2006;Paiva et al 2008;Rodrigues et al 2011aRodrigues et al , 2011bRodrigues and Machado 2012;Lange and Turner 2013;Turner and Lange 2015;Sá-Haiad et al 2015;Possobom et al 2015;Sadala-Castilho et al 2016). The close spatial relationship of plastids with the endoplasmic reticulum, as observed in the oil cavity of M. nigra, is another feature that is commonly reported for terpene glands (Sá-Haiad et al 2015 and literature therein).…”
Section: Discussionmentioning
confidence: 80%
“…The epithelial cells of mature oil glands of M. nigra share a number of common features with other metabolically active cells, such as a high density of ribosomes, a large nucleus-tocytoplasm volume ratio, and relatively small vacuoles (Fahn 1979;Evert 2006). In addition, the presence of endoplasmic reticulum tubular elements, leucoplast, and well-developed mitochondria with osmiophilic granulations has been described in glands producing terpenes (Turner et al 1999;Machado et al 2006;Paiva et al 2008;Rodrigues et al 2011aRodrigues et al , 2011bRodrigues and Machado 2012;Lange and Turner 2013;Turner and Lange 2015;Sá-Haiad et al 2015;Possobom et al 2015;Sadala-Castilho et al 2016). The close spatial relationship of plastids with the endoplasmic reticulum, as observed in the oil cavity of M. nigra, is another feature that is commonly reported for terpene glands (Sá-Haiad et al 2015 and literature therein).…”
Section: Discussionmentioning
confidence: 80%
“…The organelle composition of the epithelial cells of the canals of P. adamantinum, composed predominantly of plastids, mitochondria and smooth endoplasmic reticulum, is compatible with the synthesis of terpene resins, as observed in the secretory structures of these resins in other plant species (Gilliland et al 1988;Langenheim 2003;Rodrigues et al 2011;Sadala-Castilho et al 2016).…”
Section: Discussionmentioning
confidence: 94%
“…According to Meira et al (2014), the trichomes of Chamaecrista dentata, section Absus, secrete an oil-resin. In Vellozia intermedia and Barbacenia flava in the study area, the calyx and pedicel are covered with oil-resin glands; the stingless bees T. spinipes and Tetragonisca angustula actively collect this resin, although their visits do not result in pollination (Sadala et al, 2016). Although T. spinipes is often observed damaging the flowers of C. catharticoides (Silva, 2020), we have never recorded resin collection by these bees.…”
Section: Secretory Trichomesmentioning
confidence: 81%
“…Our results showed that in C. catharticoides and C. cathartica , the oil‐resin glands are directly involved in protection against herbivory. However, for V. intermedia , other benefits such as reduced desiccation, protection against ultraviolet rays, increased light reflection, and lowered internal temperature were suggested for the oil‐resin glands, and protection against herbivory was considered secondary (Sadala‐Castilho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%